ROLE OF DNA INTEGRITY OF SPERMATOZOA IN MALE INFERTILITY (Iraqi Journal of Medical Sciences, 2016)
Background:Classical semen analysis gives an approximate evaluation of the functional competence of spermatozoa, but not the quality of sperm DNA. With the advent of assisted reproductive technologies (ART), the concern over using damaged DNA has become apparent.Objective:To clarify the role of DNA integrity and maturity of ejaculated spermatozoa in male infertility.Methods:A randomly selected group of 50 nonazoospermic infertile patients with a history of infertility of at least 1 year duration were included in this study. Whereas control group consisted of semen samples obtained from healthy volunteers of proven fertility (n = 27). Two main assays were studied in ejaculated spermatozoa: The green Acridine Orange (AO) fluorescence test that measures DNA integrity and the terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-nick end labeling (TUNEL)- based ApopTag® technology that assesses DNA fragmentation as a late apoptotic marker. Results were compared with the standard sperm characteristics (concentration, motility and morphology) between infertile patients as well as some patients' subgroups against control donors.Results :Significant low levels of green AO fluorescent spermatozoa were observed in all patients and patient's subgroups with asthenoteratozoospermia and oligoasthenoteratozoospermia (P = 0.00001). High percentages of TUNEL-positive spermatozoa were significantly noticed, against control donors, in all patients as well as asthenoteratozoospermic and oligoasthenoteratozoo-spermic infertile patients. Interestingly, normozoospermic patients had a significantly low percentage of green AO fluorescent spermatozoa and high levels of TUNEL-positive spermatozoa versus control donors (P = 0.0005, P = 0.0069, respectively).Conclusion:From this study, it can be concluded that male infertility is associated with high rates of DNA damage in the spermatozoa, and that sperm DNA damage analysis could reveal a buried deformity of sperm nuclear DNA in infertile men classified as idiopathic, having apparently normal standard sperm parameters.Keywords:DNA denaturation, DNA fragmentation, acridine orange, TUNEL.
Keywords: DNA denaturation; DNA fragmentation; acridine orange; TUNEL